PENINGKATAN KUALITAS LINGKUNGAN PESISIR MELALUI AKSI BERSIH PANTAI DI DESA RUMAH TIGA KOTA AMBON: The Improvement Of Coastal Environment Quality Through Beach Clean-Up Program In Rumah Tiga Village, Ambon City - Marlin Chrisye Wattimena; Junita Supusepa; Frijona Fabiola Lokollo; Krisye Krisye; Eva Susan Ratuluhain; Juliana Wihelmina Tuahatu; Irma Kesaulya; Simon Tubalawony; Valentine Domaris Saleky; Fahrul Rozy Fakaubun; Imanuel Villian Trayanta Soukotta (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Contaminants entering marine systemts have become environmental issues because of their significantly negative impacts. Coasts of Rumah Tiga Village are connected to Ambon Bay and provide marine habitats and tourist attractions due to their location close to Merah Putih Bridge (including recreations, restaurants and aquaculture sites). These human related activities contribute to the discharge of wastes into marine waters. Due to their location at inshore outer Ambon Bay, marine pollutants from the bay tend to be applied at the location. Because of the concentrated pollutants at the location, the coasts of Rumah Tiga Village are a suitable location to conduct beach clean-ups in Ambon Bay. The beach clean-up activities also aim to allow Study Program of Marine Science of Faculty of Fisheries and Marine Sciences, Pattimura University to raise awareness to its students and local community to care for environment.